Experimental analysis on effect of infrared light source for moisture content test of silica sand. (2021) - Vijay Anand, L.D.; Shalini Packiam Kamala, S.; Hepsiba, D.; Ravikumar, D.; Jayapradha, A.; Marichamy, S.
Abstract: The sand properties are played an essential role in agriculture, constructions and foundry. The sand properties such as permeability, cohesiveness, adhesiveness and flow ability were affected by moisture. The moisture content test was the important role to decide the quality of the sand before processing it for any applications. Infrared (IR) light source was used to found the moisture level of sand. For these experimental investigations, silica sand was used for testing purpose. Weight loss of evaporation concept was used to found the moisture content test. It was found through the change of input factors such as infrared light power, Standoff Distance (SOD) and temperature of the heating chamber. The parametric effect was studied through regression model and variance analysis. Taguchi optimization was used to provide optimal solutions.